(untitled) (African Journal of Biomedical Research, 2024)
Gastric ulcer is a common health challenge in terms of both morbidity and mortality. In this study, male spraque dawley rats of between 180-200g weights were used. The rats were divided into 4 groups of 5 rats each; group A(control) and Group B(test control) received single dose of 40mg/kg indomethacin without treatment for four hours. Group C received 500mg/kg aqueous leaf extract of Telfairia occidentalis for 7 days without ulcer induction, while Group D (pre-treated test group) received 40mg/kg indomethacin after pre-treated with 500mg/kg aqueous leaf extract of Telfairia occidentalis daily for 7 days. At the end of the experiment, the animals were sacrificed to harvest the stomachs for laboratory analysis. Comparatively, the results revealed that Telfairia occidentalis (group D) decreased oxidative stress in group D (pretreated group), increased gastric endogenous antioxidant level in group C (extract group), and showed apparent protective effect on gastric macroscopic architecture compared to test control group B. Judging by the findings of this study, 500mg/kg aqueous leave extract of Telfairia occidentalis was gastroprotective against indomethacin induced gastric ulcerations.